Amaranthin-Like Proteins with Aerolysin Domains in Plants - Dang, Liuyi; Rougé, Pierre; Van Damme, Els J. M. (Frontiers in Plant Science, 2017)
Amaranthin is a homodimeric lectin that was first discovered in the seeds of Amaranthus caudatus and serves as a model for the family of amaranthin-like lectins. Though these lectins have been purified and characterized only from plant species belonging to the Amaranthaceae, evidence accumulated in recent years suggests that sequences containing amaranthin domains are widely distributed in plants. In this study, 84 plant genomes have been screened to investigate the distribution of amaranthin domains. A total of 265 sequences with amaranthin domains were retrieved from 34 plant genomes. Within this group of amaranthin homologs, 22 different domain architectures can be distinguished. The most common domain combination consists of two amaranthin domains followed by a domain with sequence similarity to aerolysin. The latter protein belongs to the group of β-pore forming toxins produced by bacteria such as Aeromonas sp. and exerts its toxicity by making transmembrane pores in the target membrane, as such facilitating bacterial invasion. In addition, amaranthin domains also occur in association with five other protein domains, including the fascin domain, the alpha/beta hydrolase domain, the TRAF like domain, the B box type zinc finger domain and the Bet v1 domain. All 16 amaranthin-like proteins retrieved from the cucumber genome possess a similar domain architecture consisting of two amaranthin domains linked to one aerolysin domain. Based on phylogenetic differences, 4 sequences were selected for further investigation. Subcellular localization studies revealed that the amaranthin-like proteins from cucumber reside in the cytoplasm and/or the nucleus. Analyses using qPCR showed that the transcript levels for the amaranthin-like sequences are typically low and expression levels vary among tissues during the development of cucumber plants. Furthermore, the expression of amaranthin-like genes is enhanced after different abiotic stresses, suggesting that these amaranthin-like proteins play a role in the stress response. Finally, molecular modelling was performed to unravel the structure of amaranthin-like proteins and their carbohydrate-binding sites. This study provided valuable information on the distribution, phylogenetic relationships and possible biological roles of amaranthin-like proteins in plants.